In vitro study of factors related to the hatching of eggs of Oesophagostomum columbianum - Moinuddin, MA; Begum, N; Akhter, S; Biswas, PG (Journal of the Bangladesh Agricultural University, 2011)
To determine the in vitro effects of various environmental and nutritional factors on the hatching of eggs, development and survival of larvae of Oesophagostomum columbianum, eggs were cultivated at different temperature gradients, humidity and PH in phosphate buffer saline (PBS), tap water (TW) and normal saline (NS) using serum and liver extract at different concentrations during the period from November 2008 to October 2009. In this study, no development of eggs was seen at 40C temperature within 15 days. The eggs also did not hatch while transferred to room temperature within 15 days. Hatching of eggs were maximum (38.7%) at 260C on day 5. While hatching of eggs of O. columbianum did not occur at pH 2. Maximum number of hatching of eggs was seen on day 6 (40.00%) at PH 6.5 and lowest in (3.65%) at PH 11.5. Maximum hatching of eggs (51.21%) were recorded in the relative humidity of ≥80%-90% on day 5. Light had no significant effect on the development and hatching of eggs of O. columbianum. Maximum eggs hatched in PBS containing 15% serum and 10% liver extract (42.16%) but for PBS containing 10% liver extract also produced about to same hatching rate (42.15%). The present study suggests that PBS containing 15% serum and 10% liver extract may be used as suitable media for the incubation of eggs of O. columbianum due to continuous increasing of hatching rate of eggs according to the advancement of days. Further more, for in vitro culture better results may be obtained if eggs are incubated at 260C, PH 6.5 and relative humidity ≥80%-90%. Keywords: O. columbianum; Factors; Hatching of eggs DOI: http://dx.doi.org/10.3329/jbau.v9i1.8744 JBAU 2011; 9(1): 55-60